African agricultural mechanization: Myths, realities and an emerging research agenda - Thomas Daum; Regina Birner (University of Bonn, Center for Development Research (ZEF), 2019)
African farm systems remain the least mechanized of all continents. There were substantial state-led efforts to promote agricultural mechanization during the 1960s and 1970s, but these efforts failed, which led to a subsequent neglect of mechanization, both in practice and in academia. In practice, this situation has changed more recently as governments, development practitioners and private companies have re-discovered agricultural mechanization as a top priority. In academia, scholars are also gradually devoting more effort to study mechanization. However, there is still a large gap in the literature from several decades of neglecting mechanization. In this empirical vacuum, several claims around mechanization have emerged in the public debate. While some of them are accurate, many are too simplistic and some are plainly wrong or 'myths'. Such popular myths can mislead policies and programs to promote mechanization and lead to adverse effects on farmers. This paper presents a fact check on nine propositions regarding mechanization. Which ones are true? Which ones are false? To answer these questions, the study uses most of the recent literature on mechanization, thereby also providing a review of the current literature on agricultural mechanization in Africa. The paper draws up implications for future research and action.
Keywords: J16; O12; O13; O33; Q13; Q16; Q18; 330; Agricultural Mechanization; Agricultural Intensification; Agricultural Development; Tractors; Machinery; Employment; Soil Erosion; Gender; Yield